Knowledge, Attitudes and Practices Regarding Use of Local Anaesthetics Among Non-Anaesthesia Healthcare Professionals at Mulago National Referral Hospital - Abdi, Intisar Ahmed; Kasumba, John Mark; Wabule, Agnes; Nabukenya, Mary T; Kayongo, Joseph; Kyoheirwe, Bernadette; Sheikdon, Abdirizak Abdullahi; Osman, Kamaludin D (Dove, 2024)
Abstract Intisar Ahmed Abdi,1 John Mark Kasumba,1 Agnes Wabule,1 Mary T Nabukenya,1 Joseph Kayongo,1 Bernadette Kyoheirwe,1 Abdirizak Abdullahi Sheikdon,2 Kamaludin D Osman3 1Department of Anaesthesia and Critical Care, Makerere University, Kampala, Uganda; 2Department of Orthopedics, Royal Hospital, Mogadishu, Somalia; 3Department of General Surgery, Royal Hospital, Mogadishu, SomaliaCorrespondence: Intisar Ahmed Abdi, Department of Anaesthesia and Critical Care, Makerere University, Kampala, Uganda, Tel +256762635165, Email dr.intisar16@gmail.comIntroduction: Local anaesthetics (LA) are commonly used in dental and surgical emergency wards by both anaesthesia professionals and non-anaesthesia professionals. Anecdotal evidence shows that non-anaesthesia health-care professionals do not monitor vital signs during the use of local anaesthesia, and there are no standard hospital guidelines on the use of LA and management of LA toxicity by non-anaesthesia professionals.Purpose: This study sought to assess the knowledge, attitudes and practices regarding local anaesthetic use among non-anaesthesia health-care professionals at Mulago National Referral Hospital.Patients and Methods: This was a cross-sectional study that utilized a quantitative research approach. The sample size of the study was 43 non-anaesthesia healthcare professionals from the casualty and surgical outpatient wards and Mulago dental ward. Data was collected using a questionnaire and analyzed using STATA 15.Results: Overall, 66.67% of the Specialist, 76.47% of the senior house officers, 100% of medical officers, and 80% of the clinical orthopedic house officers had unsatisfactory levels of knowledge in Mulago casualty and surgical outpatient wards. 20% of the specialist and 16.67% of the senior house officers had unsatisfactory levels of knowledge in Mulago dental ward. 87.5% of the non-anaesthesia health-care professionals do not give a test dose on a routine basis in Mulago casualty and surgical outpatient wards. A total of 63.64% of the non-anaesthesia healthcare professionals in Mulago dental ward do not sterilize the site of injection.Conclusion: Non-anaesthesia health-care professionals had unsatisfactory levels of knowledge, somewhat good practices, and negative attitudes toward LA use.Keywords: local anesthetics, LA toxicity, non-anaesthesia healthcare professionals, knowledge, attitude, practices
Keywords: local anesthetics, LA toxicity, non-anaesthesia healthcare professionals, knowledge, attitude, practices